Original paperKINEMATIC VARIABLES AND BLOOD ACID-BASE STATUS IN THE ANALYSIS OF COLLEGIATE SWIMMERS’ ANAEROBIC CAPACITY - Bielec, G.; Makar, P.; Laskowski, R.; Olek, R.A. (Biology of Sport, 2013)
Short duration repeated maximal efforts are often used in swimming training to improve lactate tolerance, which gives swimmers the ability to maintain a high work rate for a longer period of time. The aim of the study was to examine the kinematics of swimming and its relation to the changes in blood acid-base status and potassium level. Seven collegiate swimmers, with at least 6 years of training experience, volunteered to participate in the study. The test consisted of 8 x 25 m front crawl performed with maximum effort. The rest period between repetitions was set to five seconds. Blood samples were taken from the fingertip at rest, after warm-up and in the 3rd minute after completion of the test. The swimming was recorded with a video recorder, for later analysis of time, velocity and technique (stroke index). Based on the swimming velocity results, the obtained curve can be divided into rapid decrease of velocity and relatively stable velocities. The breaking point of repetition in swimming velocity was assumed as the swimming velocity threshold and it was highly correlated with the decrease of the blood acid-base status (pH r=0.82, BE r=0.87, HCO3- r=0.76; p<0.05 in all cases). There was no correlation between stroke index or fatigue index and blood acid-base status. Analysis of the swimming speed in the 8 x 25 m test seems to be helpful in evaluation of lactate tolerance (anaerobic capacity) in collegiate swimmers.